TRUST IN FRIENDSHIP: LGBTQ+ YOUNG PEOPLE AND HOOK-UP APP SAFETIES - Byron, Paul; Albury, Kath; Pym, Tinonee; Race, Kane; McCosker, Anthony (AoIR Selected Papers of Internet Research, 2019)
Digital media research commonly explores the use of social media platforms and dating/hook-up apps separately, implying distance between social and sexual communication practices. By exploring how friendships enfold into LGBTQ+ young people’s use of dating/hook-up apps, this paper troubles that delineation. In 2018, we ran four workshops with LGBTQ+ young people (18-35 years) about negotiating safety in dating/hook-up apps. Discussion of friendship featured in all workshops, mostly related to four key themes: the safety of having mutual friends with prospective dates/hook-ups; friend-making through apps; friend-involvement in safety strategies; and friendship advice on app use. Through analysis of these data, we highlight how friendship is an organising force in LGBTQ+ young people’s dating/hook-up app practices, and argue for greater attention to the porousness of media sites commonly defined as social (e.g. Instagram) or sexual (e.g. Tinder). Participants demonstrate that trust in friendship is far greater that their trust in apps, and so this is called upon, at many levels, to negotiate app use. Notably mutual friends (‘mutuals’) offer greater feelings of safety. An overlap between friendship and sexual connections is also apparent in these data, as per discussion of 'sliding into DMs'. Participants who were not cisgender men had greater concern for safety, and thus more knowledge on how to negotiate apps (and dating) safely, particularly through friendship support networks.